Factors influencing saving behaviour (in view of retirement): A study on Petronas Chemicals Marketing (Labuan) Ltd PCML employees / Muhammad Abdullah - Abdullah, Muhammad (2016)
Awareness in retirement is still an indistinct matter among people in Malaysia and many retirement products being introduced by financial institutions and yet the initiatives to put aside for retirement are step sided by many. Since the majority think that companies and government retirement plan should be sufficient to cover for golden years costs. Yet, many studies have revealed that money saved in companies and government pension plan may not be enough for future expenditure.